The Role of Parents as Advocates for the Transition Rights of Their Disabled Youth - Austin, James (Disability Studies Quarterly, 2000)
This article describes the need for parents to be equal partners in the transition programming of their disabled child. Parents play a crucial role in the lives of their disabled children even after their son or daughter has made the transition to adulthood. Parents have a role to play in ensuring that the rights mandated to their disabled children by Federal law are made available to them. Parents can assist in making sure their children understand the services available to them after they leave school. Several barriers to parent participation are discussed and strategies offered to empower parents to serve as advocates for their son or daughter.